2018
DOI: 10.1007/s12020-018-1760-8
|View full text |Cite
|
Sign up to set email alerts
|

Universal vs. risk-factor-based screening for gestational diabetes—an analysis from a 5-Year Portuguese Cohort

Abstract: Purpose The criteria to screen for Gestational Diabetes Mellitus are not internationally consensual. In opposition to the universal screening performed in Portugal, certain countries advocate a risk-factor-based screening. We aim to compare obstetric and neonatal outcomes in pregnant women with and without risk factors treated for Gestational Diabetes Mellitus. Methods Retrospective and multicentric study of 12,006 pregnant women diagnosed with Gestational Diabetes Mellitus between 2011 and 2015, in Portugal. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…The high costs and technical challenges of the OGTT have resulted in many countries using risk factor-based selective screening, followed by OGTT diagnosis, as the cornerstone of GDM diagnosis [6]. Unfortunately, the currently available risk factors (overweight or obesity, excessive gestational weight gain, advanced maternal age, family history of diabetes, previous history of GDM, and adverse pregnancy outcomes) have poor predictive value and fail to identify a large percentage of women with GDM, thus limiting their use as screening tools [29,35,36]. Therefore, the identification of novel risk factors or biomarkers that could be targeted to prompt OGTT screening and GDM diagnosis has become an increasing focus of GDM research.…”
Section: Gestational Diabetes Mellitusmentioning
confidence: 99%
“…The high costs and technical challenges of the OGTT have resulted in many countries using risk factor-based selective screening, followed by OGTT diagnosis, as the cornerstone of GDM diagnosis [6]. Unfortunately, the currently available risk factors (overweight or obesity, excessive gestational weight gain, advanced maternal age, family history of diabetes, previous history of GDM, and adverse pregnancy outcomes) have poor predictive value and fail to identify a large percentage of women with GDM, thus limiting their use as screening tools [29,35,36]. Therefore, the identification of novel risk factors or biomarkers that could be targeted to prompt OGTT screening and GDM diagnosis has become an increasing focus of GDM research.…”
Section: Gestational Diabetes Mellitusmentioning
confidence: 99%
“… 80 A more recent retrospective study in more than 12,000 women confirmed that women with GDM diagnosed according to the IADPSG criteria without risk factors had fewer obstetric and neonatal complications compared with those having risk factors. 82 In contrast, several studies showed that missed GDM cases without risk factors had worse pregnancy outcomes than women without GDM. 77 , 78 For example, data from the Irish ATLANTIC-DIP study reported that selective screening based on risk factors in a Caucasian population missed 20% (using National Institute for Health and Care Excellence (NICE) criteria), 16% (following Irish guidelines), and 5% (with ADA guidelines) of women diagnosed with GDM using IADPSG criteria.…”
Section: Overview Of the Included Publicationsmentioning
confidence: 99%
“…The primary healthcare services, which are generally the first port of call for pregnant women, are often fraught with difficulties, from problems with access to lack of continuity of care and understaffing, bringing into question the true appreciation of the disease burden. While risk factor-based screening remains the cornerstone of screening strategies in LMICs owing to its cost and ease, numerous studies [37,38] have demonstrated the poor predictive value of this approach to screening, with a local study [28] showing that 10.6% of HFDP cases would have been missed.…”
Section: In Practicementioning
confidence: 99%